THE ANALYSIS OF LEARNING AND BEHAVIOR: SKINNER’S LAW OF POSITIVE REINFORCEMENT - Turdiyeva Zahro Mirsoliyevna, (TADQIQOTLAR, 2025)
This article explores the theories of Burrhus Frederic Skinner, particularly his work  on  operant  conditioning  and  its  application  in  educational  settings.  Skinner's emphasis on positive reinforcement and structured, error-free learning materials has significantly influenced classroom management and teaching practices, especially for students with learning difficulties. The article also highlights objections to Skinner's theory, such as the undervaluation of risk-taking and failure as essential components of learning, the reduction of learning processes to conditioning, and concerns about over-reliance  on  external  rewards.  The  discussion  further  contrasts  Skinner's behaviorist  approach  with  contemporary  educational  philosophies  emphasizing intrinsic motivation, concept development, and the invisible aspects of learning.